Pengaruh Shopping Lifestyle dan Fashion Involvement terhadap Impulse Buying Behavior Masyarakat Kota Bima (Studi Kasus Pada Penggemar Hijab Umama) - Nila rizkia; Ita Purnama (Journal of Creative Student Research, 2023)
This research aims to determine the influence of Shopping lifestyle and Fashion Involvement on the Impulse Buying Behavior of the People of Bima City. In this research, the type of associative research is used, namely research that is to find out the relationship between two or more variables and in this research the researcher wants to know the relationship between the variables shopping lifestyle (X1), fashion involvement (X2), and the variable impulse buying behavior (Y). The population used in the research was all the people of Bima City who had worn the unknown number of the Umama brand hijab (unknown population) and used a purposive sampling technique. The sampling in this research was 100 respondents. The research instrument uses a Likert scale using validity tests, reliability tests, classical assumption tests, multiple linear regression, correlation coefficient analysis (R), determination coefficient analysis (R2), t test and f test. The research results show that 1) There is a significant influence of shopping lifestyle on the impulse buying behavior of the people of Bima City. 2) There is no significant influence of fashion involvement on the impulse buying behavior of the people of Bima City. 3) Shopping lifestyle and fashion involvement together have a significant influence on the impulse buying behavior of the people of Bima City.